The role of SOCT in monitoring the course of disease and modification of treatment in Birdshot chorioretinopathy – two years of clinical observation - Grzymowicz-Leciak, Magdalena; Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
The aim of the article is to present the role of SOCT in monitoring the treatment of Birdshot chorioretinopathy based on a clinical case. A 78 years old woman with Birdshot retinopathy was referred to the Department of Ophthalmology for visual deterioration since 2 months. The patient complained about blurred vision and floaters. Eye examination revealed changes on the fundus typical for birdshot chorioretinopathy. Two years of regular checking and SOCT scans allowed for better monitoring and modification of treatment both with steroids and with non steroid immunosuppressive agents. Finally, based on the changes at the vitreo- -retinal interface revealed in SOCT examination, the patient was treated with PPV with satisfactory functional and anatomic results.